Study of Dimorphism of Humerus in Maharashtra Population - Mohammad Abdul Mateen (Indian Journal of Forensic Medicine & Toxicology, 2020)
45 male and 45 females right and left dried, non pathological humerus were measured with vernier caliper and weighed with digital weighing machine. The vertical diameter of superior articular surface, transverse diameter of superior articular surface, circumference of superior articular surface, circumference of mid shaft in males and females of right and left humerus were studied and found highly significant P values in both sexes and right left humerus (P<0.01). These parameters will be quite useful to medico- legal expert, anthropologist because morphometric values of mesoderm are uncertain.